From C(sp2)-H to C(sp3)-H: systematic studies on transition metal-catalyzed oxidative C-C formation - Li, Bi-Jie; Shi, Zhang-Jie (Chemical Society reviews, 2012)
In this tutorial review, we will summarize our recent efforts in transition metal-catalyzed oxidative coupling via C-H functionalization of aromatic, benzylic and allylic C-H bonds. Related works from other laboratories will be cited where suitable, aiming to give the readers a flavor of this field. Special emphasis is placed on the reaction design and development. Our recent developments in transition metal-catalyzed oxidative coupling via C-H functionalization of aromatic, benzylic and allylic C-H bonds is summarized.